Answer:
y = -6/5x + 3
Step-by-step explanation:
y = mx + c (or b, depending on where you're from)
Slope = m = -6/5
y = -6/5x + c
You can sub (0, 3) and (5, -3) into y = -6/5x + c and they both have the same answer where c = 3
Therefore, the equation is y = -6/5x + 3
Hop this helps
Answer:
slope = -1
Step-by-step explanation:
y2-y1 divided by x2-x1
3-7= -4
2-(-2) = 4
-4 divided by 4 = -1
Answer:
5 cupcakes
Step-by-step explanation:
=1x 30/ 6
=5
I hope it helps
Thank U
58.51%
however, it is estimating so depending on the answer choices it would be around 55-60% or so
Answer:
A and C luv <3
Step-by-step explanation: